Evaluation of the ecological civilization index of China based on the double benchmark progressive method. (10th June 2019) - Zhang, Linbo; Yang, Jiao; Li, Daiqing; Liu, Haijiang; Xie, Yuxi; Song, Ting; Luo, Shanghua
Abstract: Since 2013, the Chinese government has issued a set of action plans catered toward the ecological civilization construction. To quantify and evaluate the ecological civilization development, this study has introduced the ecological civilization index of China (ECI), using different standardization methods (extreme standardization, single-benchmark progressive standardization, and double benchmark progressive standardization), to evaluate ecological civilization development on city-level (337 cities) of China. The issues of China's ecological civilization construction were analyzed. The evaluation results suggest that in the double benchmark progressive method, every evaluation score has its practical meaning and is therefore suitable for policy making. This study obtained an average ECI score of 61.16, for 337 cities. This is China's overall ECI score, which is classified as C-grade. Only 4.75% of cities' green environment (GE) score obtained A-grade, while 53.41% of cities' GE scored below the passing level, suggesting that the quality of the ecology and environment is neglected in the development of China eco-civilization. This study provides valuable knowledge for both the ecological and environment management and eco-civilization construction. Highlights: China's overall level of the ecological civilization development is not optimistic. China's ecological civilization development is uneven in spatial distribution. Ecology and environmental quality were still the short board of China's Eco-civilization construction. The ecological civilization development in the main production areas of agricultural products lags other functional areas.